Outbreak of Bacterial Meningitis Among Patients Undergoing Myelography at an Outpatient Radiology Clinic - Chitnis, Amit S. (J Am Coll Radiol, 2012)
PURPOSE: To investigate an outbreak of bacterial meningitis at an outpatient radiology clinic (clinic A) and to determine the source and implement measures to prevent additional infections. METHODS: A case was defined as bacterial meningitis in a patient undergoing myelography at clinic A from October 11 to 25, 2010. Patients who underwent myelography and other procedures at clinic A during that period were interviewed, medical records were reviewed, and infection prevention practices were assessed. Case-patient cerebrospinal fluid (CSF) specimens, oral specimens from health care personnel (HCP), and opened iohexol vials were tested for bacteria. Bacterial isolates were compared using pulsed-field gel electrophoresis. A culture-negative CSF specimen was tested using a real-time polymerase chain reaction assay. RESULTS: Three cases were identified among 35 clinic A patients who underwent procedures from October 11 to 25, 2010. All case-patients required hospitalization, 2 in an intensive care unit. Case-patients had myelography performed by the same radiology physician assistant and technician on October 25; all patients who underwent myelography on October 25 were affected. HCP did not wear facemasks and reused single-dose iohexol vials for multiple patients. Streptococcus salivarius (a bacteria commonly found in oral flora) was detected in the CSF of 2 case-patients (1 by culture, 1 using real-time polymerase chain reaction) and in HCP oral specimens; 1 opened iohexol vial contained Staphylococcus epidermidis. Pulsed-field gel electrophoresis profiles from the case-patient S salivarius and the radiology physician assistant were indistinguishable. CONCLUSIONS: Bacterial meningitis likely occurred because HCP performing myelography did not wear facemasks; lapses in injection practices may have contributed to transmission. Targeted education regarding mask use and safe injection practices is needed among radiology HCP.